Pengaruh ukuran perusahaan, profitabilitas, leverage, efisiensi biaya, umur perusahaan dan ukuran dewan pengawas syariah terhadap Islamic social reporting pada perbankan syariah di Indonesia periode 2016-2020 - Debi Rahmawati; Tenny Badina; Rita Rosiana; Ahmad Fatoni (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2022)
This study aims to explain the variables of firm size, profitability, leverage, cost efficiency, firm age, size of the sharia supervisory board in influencing Islamic Social Reporting. The population in this study is Islamic banking in Indonesia which is registered with the Financial Services Authority (OJK) for the period 2016 – 2020. The data used in this study is panel data from 10 samples of selected companies, with a total sample of 50. Company size and company age have a negative and significant effect on ISR. The size of the sharia supervisory board has a positive and significant effect on ISR. Meanwhile, profitability, leverage, and cost efficiency have no significant effect on ISR.